Pneumonia due to a Rare Pathogen: Achromobacter xylosoxidans, Subspecies denitrificans - Hesham Awadh; Munthir Mansour; Obadah Aqtash; Yousef Shweihat (Case Reports in Infectious Diseases)
Achromobacter xylosoxidans, subspecies denitrificans, is a gram-negative rod recently implicated as an emerging cause of infection in both immunosuppressed and immunocompetent populations. Few cases are reported in literature involving multiple body systems. Diagnosis depends on cultures of appropriate specimens, and management usually is by administration of appropriate antibiotics (usually agents with antipseudomonal activity). We report a rare case of pneumonia due to infection with this organism, in a patient with preexisting bronchiectasis secondary to chronic aspiration.